TRANSFORMASI DIGITAL DALAM PENGEMBANGAN SUMBER DAYA INSANI: ANALISIS PERBANDINGAN INDONESIA DAN DUNIA - Karmila Sari; Taufik Ramadhan Sy; Angga Rizki Prawira; Sandra Dewi (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2026)
The acceleration of global digital transformation has reshaped the landscape of human capital development, demanding new competencies, adaptive leadership, and rapid organizational change. Indonesia, as one of the fastest-growing digital economies in Southeast Asia, faces structural opportunities and challenges in strengthening its human capital to remain competitive in global markets. This paper analyzes the dynamics of digital transformation in shaping human capital development in Indonesia compared with global practices, drawing upon frameworks from the World Economic Forum, OECD, McKinsey, and international human capital development models. Using a qualitative descriptive approach supported by secondary data, this study finds that Indonesia’s human capital transformation is progressing but still constrained by digital skill gaps, unequal access to digital infrastructure, and insufficient integration between industry needs and education systems. Meanwhile, global leaders—such as Finland, Singapore, South Korea, and Germany—demonstrate successful models of competency-based education, lifelong learning ecosystems, and strong digital governance. This comparative analysis concludes that Indonesia must accelerate digital skill mastery, strengthen cross-sector collaboration, and adopt globally tested frameworks to optimize human capital readiness for the digital economy.